A comparative study of the effect of two oral health education promotion materials among Grade I pupils of Sta. Rita Elementary School in Aringay, La Union, SY 2001-2002 - Zarate, Jane Kenneth E.
The effectiveness of two methods of oral health education promotion for improving oral health knowledge and practice among Grade One pupils in Sta. Rita Elementary School in Aringay, La Union was evaluated. Twenty-five 6-8 year old pupils were assigned to one of two groups. In one group, the pupils received a lecture only on dental health knowledge and practice, and the other group received a lecture and demonstration on dental health knowledge and practice. Knowledge is measured in terms of pre-test (PTK), immediate post-test (IPTK) and delayed post-test (DPTK) after a week using the same questionnaire. Practice is evaluated by the actual performance of the pupils on dental hygiene through measuring OHI-S before (PA) and one week after the intervention (DPA). The PTK, IPTK, DPTK, PA and DPA were compared. After the intervention, all the pupils in both groups displayed significant improved knowledge and practice on dental health as seen in the scores from pre-test to delayed post-test. It was also shown in this study that the group who received the lecture plus demonstration had a higher percentage of OHI-S improvement than the group who received the lecture only. Although both the methods of teaching oral health are shown effective in the study, the results suggest that the provision of demonstration and return demonstration is the more effective means of promoting oral health for the Grade 1 pupils.